ANALISIS KEBUTUHAN TERHADAP MANAJEMEN BIMBINGANDAN KONSELING DALAM BIDANG BELAJAR (AKADEMIK) BAGI SISWA SMKN 2 KUALA KAPUAS - Nurmaryam Nurmaryam; Siminto Siminto (CV. ADIBA ASIHA AMIRA, 2023)
This study aims to understand some of the needs for Guidance and Counseling Management, especially in the field of learning (Academic) at SMKN 2 Kuala Kapuas. This observation uses a qualitative descriptive method. The results of the analysis of this study show that the need for guidance and counseling management in the field of learning for students at SMKN 2 Kuala Kapuas is adjusted to the regulation of the Minister of Education Number 111 of 2014 concerning guidance and counseling which includes basic services, responsive services, specialization services and individual participant planning education and system support. In the implementation of the guidance and counseling program, the methods carried out are according to previously formulated activity programs such as classical guidance, group counseling, individual counseling or group counseling as well as other methods that support BK activities such as case conferences, home visits, advocacy, consultations and case transfers (referrals). As for the management of Guidance and Counseling in the field of learning (academic) at SMKN 2 Kuala Kapuas it is more focused on the Individual Consultation and Counseling method. Factors supporting the management of guidance and counseling in the field of learning (academic) at SMKN 2 Kuala Kapuas in essence really need a good understanding of the entire academic community, both from the principal and teachers so that the implementation of guidance and counseling can run effectively and efficiently. In addition, the participation of students in working with guidance and counseling teachers makes the implementation more effective. In addition, the availability of facilities that are quite complete both in terms of guidance and counseling facilities and infrastructure is also a supporting factor in Counseling Guidance services, especially in the field of learning (academic). The inhibiting factor in Counseling Guidance services in the field of learning is the lack of openness of some students about the problems they are facing. In addition, the very limited time allocation for the inclusion of BK Subjects in the class schedule is an inhibiting factor in the implementation of guidance and counseling, so that during the implementation of guidance and counseling, only use the sidelines of free time such as recess.